Dynamic fragmentation of melted metals upon intense shock wave loading. Some modelling issues applied to a tin target - Signor, L.; Dragon, A.; Roy, G.; de Rességuier, T.; Llorca, F. (Archives of Mechanics, 2008)
We are interested in the dynamic fragmentation event produced in shock-melted metals called micro-spalling. Global energetic approach is briefly reviewed. It provides a general modelling framework that leads to realistic fragment-size predictions. But the actual physical mechanisms involved remain poorly understood. We attempt to explore the conditions under which cavitation, i.e. nucleation and growth of microvoids, may be responsible for fragmentation. This cavitation process is described by means of a hollow sphere model whose matrix is made of liquid tin.